DEVELOPMENT OF ANDROID AND WEB-BASED RENTAL INFORMATION SYSTEM FOR GRAHA MUSTIKA HALL INTEGRATED WITH PAYMENT GATEWAY - Chalim, Noor; Setiawan, Rhoedy; Irawan, Yudie; Darmanto, Eko (Jurnal Disprotek, 2025)
Graha Mustika Building in Getaspejaten Village, Jati District, Kudus Regency, is usually used for various events including weddings and meetings. However, the rental process of this building is still done manually, starting from checking the schedule to confirming payment, previous research shows that the existing web-based rental system is not fully effective due to several problems, such as an unresponsive display, no features to add equipment, no transaction process security, no vendor registration feature, unclear schedule information. This causes problems such as difficulty finding fast and inaccurate information, misuse of schedules, vendors must come in person if they want to join, This study aims to develop an Android-based rental information system and a website that is integrated with a payment gateway to make it easier for prospective tenants, vendors and building managers to manage the rental process. This system provides features for checking building availability in real-time, submitting rentals, and processing payments with a payment gateway. The data stored in the system includes rental prices, transactions, tenants, schedules, and equipment. The methods used in system design are Extreme Programming and Unified Modeling Language. Through the system created, it is expected to improve the accuracy of recording, transparency, and efficiency in the management of the Graha Mustika Building, thereby reducing the risk of errors that often occur in manual systems.Gedung Graha Mustika di Desa Getaspejaten, Kecamatan Jati, Kabupaten Kudus, biasa digunakan dalam berbagai acara antara lain pernikahan dan pertemuan. Namun, proses penyewaan gedung ini masih dilakukan secara manual, mulai dari pengecekan jadwal hingga konfirmasi pembayaran, penelitian sebelumnya menunjukkan bahwa sistem penyewaan berbasis web yang ada tidak sepenuhnya efektif karena beberapa masalah, seperti tampilan yang tidak responsif, tidak ada fitur untuk menambah perlengkapan, tidak adanya keamanan proses transaksi, belum ada fitur daftar sebagai vendor, informasi jadwal yang tidak jelas. Hal ini menyebabkan masalah seperti kesulitan mencari informasi yang cepat, dan kurang akurat, penyalahgunaan jadwal, vendor harus datang langsung kalau mau bergabung, Penelitian ini bertujuan untuk mengembangkan sistem informasi penyewaan berbasis Android dan website yang terintegrasi dengan payment gateway untuk mempermudah calon penyewa, vendor dan pengelola gedung dalam mengelola proses penyewaan. Sistem ini menyediakan fitur pengecekan ketersediaan gedung secara real-time, pengajuan penyewaan, dan pemrosesan pembayaran dengan payment gateway. Data yang disimpan dalam sistem meliputi harga sewa, transaksi, penyewa, jadwal, dan perlengkapan. Metode yang digunakan dalam perancangan sistem adalah Extreme Programming dan Unified Modeling Language. Melalui adanya sistem yang dibuat, diharapkan dapat meningkatkan akurasi pencatatan, transparansi, serta efisiensi dalam pengelolaan Gedung Graha Mustika, sehingga mengurangi risiko kesalahan yang kerap terjadi pada sistem manual.